Oráculos da saúde: análise das (novas) relações de consumo e cuidados com a saúde nos laboratórios da medicina personalizada - Holtz, Ana Catarina dos Santos (2023)
In this work, we address the new consumer relations and health care from the emergence of what we are calling Personalized Medicine, aiming to problematize, from the perspective of biopower and biopolitics based on the logic of consumption, how the construction of (new) relationships between consumption and health care are happening. We start from the following research problem: how are the (new) relationships of consumption and health care built, notably related to personalized medicine, from the perspective of biopower and biopolitics considering the logic of consumption? To address this issue, we used as basis the theoretical precepts of Foucault, Rose, Ortega, Sibilia, Rocha, Hoff and Mazzilli. Based on these authors, we analyzed two laboratories that exemplify the characteristics of Personalized Medicine: the Jackson Laboratory, focused on genomic research; and the Brazilian Genera, specialized in what it calls “recreational genetics”. After exploratory research on the communication of these laboratories, we selected as corpus the institutional materials composed of videos, websites and posts on social networks – which we analyzed according to the theoretical-methodological inspiration of Foucault's genealogy. As a result, we found signs of new configurations of the relationship between health and body, with a biopower moving towards the fragmentation of the body, more focused on intervention at the genetic level; and a multidirectional biopolitical strategy, which uses several specialists to govern consumer behavior, centered on market practices – mainly in biomedical laboratories, such as the two ones studied in this thesis.